2014
DOI: 10.1111/cei.12410
|View full text |Cite
|
Sign up to set email alerts
|

Associations of single nucleotide polymorphisms in precursor-microRNA (miR)-125a and the expression of mature miR-125a with the development and prognosis of autoimmune thyroid diseases

Abstract: SummaryIt is important to search the biomarker to predict the development and prognosis of autoimmune thyroid diseases (AITDs) such as Hashimoto's disease (HD) and Graves' disease (GD). MicroRNA (miR) bind directly to the 3′ untranslated region of specific target mRNAs to suppress the expression of proteins, promote the degradation of target mRNAs and regulate immune response. miR-125a is known to be a negative regulator of regulated upon activation normal T cell expressed and secreted (RANTES), interleukin (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 25 publications
(40 reference statements)
3
27
0
2
Order By: Relevance
“…1A, rs12976445 polymorphism is located 54 bp upstream of pre-miR-125a. Although the in silico analysis indicated that rs12976445 polymorphism could alter neither the predicted secondary structure nor the predicted ΔG, the northern blot results demonstrated that the presence of the minor allele of rs12976445 polymorphism significantly changed the ratio of pre-miR-125a and mature miR-125a, suggesting that the polymorphism significantly interfered with the mature processing of the miRNA [20]. In this study, we collected 54 tissue samples genotyped as CC (n=32), CT (n=18), and TT (n=4) and performed real-time PCR and western blot analysis to determine the expression levels of the miRNA and the gene.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…1A, rs12976445 polymorphism is located 54 bp upstream of pre-miR-125a. Although the in silico analysis indicated that rs12976445 polymorphism could alter neither the predicted secondary structure nor the predicted ΔG, the northern blot results demonstrated that the presence of the minor allele of rs12976445 polymorphism significantly changed the ratio of pre-miR-125a and mature miR-125a, suggesting that the polymorphism significantly interfered with the mature processing of the miRNA [20]. In this study, we collected 54 tissue samples genotyped as CC (n=32), CT (n=18), and TT (n=4) and performed real-time PCR and western blot analysis to determine the expression levels of the miRNA and the gene.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, TP53INP1, as well as the apoptosis status of the host cells [36], has been reported to be under the control of the miRNAs [37]. Hu et al reported that rs12976445 polymorphism in the pri-miR-125a causes a significant reduction in the amount of mature miR-125 by compromising the mature processing of the miRNA, leading to less efficient inhibition of target genes, LIFR, and an increased risk of recurrent pregnancy loss in a Chinese population [20]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al found that MIR125A rs12976445 C/T was significantly associated with HD and intractable GD (131). Our recent study also proved that rs3746444 of miR-499a and rs12976445 of miR-125a-5p were associated with AITD susceptibility (153).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%
“…MiR-125a is recognized to be a negative regulator of Kruppel-like factor 13 (KLF13), and the tumor necrosis factor-a-induced protein 3 (TNFAIP3) prevents the production of regulated activation of normal T cell and secreted (RANTES), and stimulates the nuclear factor kappa B (NFkB) pathway. The MiR125A gene, which encodes miR-125a, is located on chromosome 19q13.41 [14].…”
Section: Introductionmentioning
confidence: 99%